Positive Religious Coping and Mental Health among Christians and Muslims in Response to the COVID-19 Pandemic - Thomas, Justin; Barbato, Mariapaola (Religions (Basel, Switzerland ), 2020)
Positive religious coping has frequently been associated with better mental health outcomes when dealing with stressful life events (e.g., natural disasters, domestic abuse, divorce). The COVID-19 pandemic, and the associated infection prevention and control measures (curfew, quarantine, restricted travel, social distancing), represent a society-wide stressor. This study explored positive religious coping among the Muslim and Christian residents of the United Arab Emirates (UAE) during the early stages of the national response to the COVID-19 pandemic. Participants (N = 543) completed an online survey assessing religious coping in response to the pandemic, along with symptom measures of depression, anxiety and history of psychological disorder. Muslims (N = 339) reported significantly higher levels of positive religious coping compared to their Christian counterparts (N = 204). Across the whole sample, positive religious coping was inversely related to having a history of psychological disorders. Among the Muslim cohort, positive religious coping was inversely related to depressive symptoms and having a history of psychological disorders. Positive religious coping during infectious disease outbreaks may help some individuals reduce their risk of depressive illness. National pandemic preparedness plans may benefit from including a focus on religion and religious coping.